In vitro percutaneous permeation of repellent picaridin and sunscreen oxybenzone - Chen, Ting (2010)
In this thesis, a series of in vitro diffusion studies were performed to evaluate the transmembrane permeation of picaridin and oxybenzone across human epidermis and poly(dimethylsiloxane) (PDMS) membrane. Transdermal permeation of picaridin and oxybenzone from four commercially available repellent and sunscreen products was also investigated by using different application concentrations and sequences. The results obtained were then compared to those of the repellent DEET and the sunscreen oxybenzone under identical experimental conditions. Permeation of picaridin and oxybenzone across human epidermis was suppressed when both compounds were used concurrently. Increasing concentration of the test compounds further reduced the permeation percentage of picaridin and oxybenzone. While permeation characteristics were correlative between human epidermis and artificial PDMS membrane, permeability of PDMS membrane was significantly larger than that of human epidermis. This finding was different from concurrent use of DEET and oxybenzone in which a synergistic permeation enhancement was observed between the two substances. Transdermal permeation of picaridin across human epidermis from various commercially available spray preparations was significantly lower than that of DEET from similar spray products, both alone and in combination with sunscreen oxybenzone. Concurrent application of the commercial products resulted in either no change or suppression of permeation of picaridin and oxybenzone. This finding was also different from concurrent application of DEET and oxybenzone using commercial preparations. In addition, permeation of picaridin and oxybenzone across human epidermis was dependent on application concentration, use sequence, and preparation type.It was concluded from this thesis that picaridin would be a better candidate for concurrent application with sunscreen preparations in terms of percutaneous permeation.